The Role of Islamic Society in the Ecological Management and Sustainable Development - Budi Susetyo; Rimun Wibowo; Mohammad Ar Radi; Hafiz Taqwa (Jurnal Rekayasa Lingkungan dan Biosistem, 2024)
The phenomenon of environmental damage is a very serious global issue and an increasingly complex problem. This damage is due to the exploitation of excess economic value without considering future sustainability (over exploitation). This happened after humans practiced the capitalist economy while ignoring Islamic values. Various efforts to overcome this environmental damage have been carried out, including various policies and regulations that regulate human activities in interacting with their environment as measured by the achievements of SDG's (Sustainable Development Goal's). Experts have also tried various applications of concepts and theories as well as models of approaches and technologies that are possible to overcome the problem. These efforts so far have not significantly paid off, in fact, tending to increase the level of environmental damage. The idea of returning to the application of religious values and spirituality is one of the alternatives that needs to be applied through a holistic approach. The purpose of writing this article is to develop a model of the role of Islamic society in environmental management and sustainable development. Exploratory methods are used to map the role of Islamic communities in environmental restoration and rehabilitation movements, eco-islamic boarding school, and non-governmental organizations that are active in the community and also through Islamic dawah content. The results showed that there is a significant role that can be used as a role model, so that it can be replicated by other Islamic societies around the world.